Development of hydraulic system for multidisciplinary design - Ng, Patrick Lian Sheng (2015)
The project calls for the application of engineering knowledge to design, develop and fabricate a device that utilises the hydraulic system. The choice of designing and developing a prototype of a sit-to-stand device was made because this is a frequent daily activity, and the ability to do so will add to mobility and independence for individuals, especially the elderly and persons with disabilities who are likely to grow in numbers with ageing of the population. The inquiry as part of the project includes a study of dining chairs and the hydraulic mechanisms to perform the lift and tilt functions of the assistive device. The studies provided information for design and development of the assistive device. Within the budget allocated to the project, a sit-to-stand device using the hydraulic car jack was fabricated in-house that will lift the back portion of the dining chair to an angle to allow the feet of the user to be firmly on the floor and reach an inflexion point for the user to extend and stand up. Testing of the assistive device showed that the prototype was able to lift persons of 65 kg to 130 kg with insignificant differences in timing to reach the point of standing up. The prototype, however, is based on a fundamental design with no bells and whistles. It can certainly be further finetuned to improve its functionality, aesthetics, and costs, especially when looking towards commercialisation of the device. In addition, as the device is targeted for use by vulnerable persons such as the elderly and persons with disability, market research and clinical studies may need to be undertaken to evaluate potential demand and evidence-based results of effectiveness, efficiency and safety of the assistive device.